Revisiting innovation adoption theory through electronic public relations. Issue 1 (5th February 2018) - Panopoulos, Anastasios; Theodoridis, Prokopis; Poulis, Athanasios
Abstract : Purpose: The purpose of this paper is to shed light on the innovation adoption process taking place in the public relations field through the use of Web 2.0 applications and social network activities. Design/methodology/approach: Innovation adoption of electronic public relations (E-PR) is examined at personal, organizational, and environmental levels by employing, for each one of the previous, a number of different sub-dimensions leading to the creation and verification of a hierarchical tree structure. Findings: E-PR innovation adoption can be influenced at personal, organizational, and environmental levels. Each of the aforementioned levels is hierarchically linked to a number of factors that can actually speed up the process. Originality/value: Never before to the authors' knowledge the E-PR adoption process was examined as a hierarchical model bridging the innovation adoption literature with the public relations literature.